2017
DOI: 10.17219/acem/61044
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of erythropoietin on Alzheimer’s dementia model in rats

Abstract: Background. Although Alzheimer's disease (AD) is the most common age-related neurodegenerative disease and characterized by memory impairment, only symptomatic treatments are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…EPO binds to EPO receptors (EPOR) on the surface of the erythroid progenitor cells to stimulate erythropoiesis in the bone marrow [18,19] and is clinically used to treat anemia [20,21]. Besides its role in erythropoiesis, EPO is a neurotrophin and offers therapeutic benefits in mouse models of neural diseases [22], and in the past decade, numerous studies have reported the protective effects of chronic rhu‐EPO dosing in experimental AD [23–28]. Given the role of EPO in proliferation and differentiation of erythroid progenitor cells, hematopoietic side effects are the major concern associated with chronic rhu‐EPO use; however, only a small number of studies report the hematopoietic effects of chronic rhu‐EPO use in experimental AD [24].…”
Section: Discussionmentioning
confidence: 99%
“…EPO binds to EPO receptors (EPOR) on the surface of the erythroid progenitor cells to stimulate erythropoiesis in the bone marrow [18,19] and is clinically used to treat anemia [20,21]. Besides its role in erythropoiesis, EPO is a neurotrophin and offers therapeutic benefits in mouse models of neural diseases [22], and in the past decade, numerous studies have reported the protective effects of chronic rhu‐EPO dosing in experimental AD [23–28]. Given the role of EPO in proliferation and differentiation of erythroid progenitor cells, hematopoietic side effects are the major concern associated with chronic rhu‐EPO use; however, only a small number of studies report the hematopoietic effects of chronic rhu‐EPO use in experimental AD [24].…”
Section: Discussionmentioning
confidence: 99%
“…EPO and its receptors are found in the CNS of mammals, and are essential for neurodevelopment, adult neurogenesis, and neuroprotection. In animal models of neurodegenerative diseases including AD, neuroprotective and neuroregenerative mechanisms of EPO are related to inhibiting apoptosis, reducing oxidative stress and inflammation, promoting the angiogenesis and neurogenesis, and maintaining blood brain barrier (BBB) integrity [ 31 ]. The latter effect might be especially important mechanism in OXYS model due to neurovascular disturbances registered in OXYS rats [ 10 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the idea that studies of adult neurogenesis in animal models of AD provided a great variability in results, which was dependent on experimental conditions, the age or promoter studied, and though neurogenesis was decreased and increased in its dependence of study conditions (reviewed in [140,141]), most strategies focused on the induction of neurogenesis. Adult neurogenesis can be stimulated through extrinsic administration of chemical agents and growth factors in the context of AD, such as: Erythropoietin [142,143,144], fluoxetine [145], granulocyte colony stimulating factor (G-CSF) and AMD3100 [146], brain-derived neurotrophic factor (BDNF) [147,148,149], insulin growth factor-1 (IGF-1) [150], nerve growth factor (NGF) [151,152], vascular endothelial growth factor (VEGF) [153], growth, and transforming growth factor β (TGF-β) [154]. In addition, neurogenesis becomes stimulated by voluntary running and physical exercise, as well as an enriched environment [155,156,157,158].…”
Section: Stem Cell Therapiesmentioning
confidence: 99%